Acral lentiginous melanoma: Clinicopathologic and survival differences according to tumour location. (3rd May 2020) - Howard, Matthew; Xie, Charles; Wee, Edmund; Wolfe, Rory; McLean, Catriona; Kelly, John W.; Pan, Yan
Abstract: Background/Objectives: Acral lentiginous melanoma (ALM) is a melanoma subtype associated with atypical locations on the hands and feet and advanced disease at diagnosis. There is a limited understanding of whether the survival is similar for nail, non‐nail, lower limb and upper limb ALM patients. We therefore explored clinicopathologic characteristics and melanoma‐specific survival of ALM patients according to tumour location. Methods: A prospectively collected cohort study was performed of all primary invasive cutaneous acral lentiginous melanomas with known thickness and tumour location reviewed at a tertiary referral centre over 21 years. Results: A total of 101 ALM patients were reviewed from 1994 until 2016. The majority of cases (82/101) occurred on the feet. Hand ALMs were thicker and more likely to be ulcerated than feet ALMs ( P = 0.05 and 0.02, respectively); however, survival was not statistically different between these two groups (univariate HR 0.48 P = 0.11, 95% CI, 0.20–1.17; multivariate HR 0.67 P = 0.40, 95% CI, 0.27–1.69, respectively). Non‐nail ALM patients had longer survival when compared to nail ALM on univariate analysis (HR 0.40, 95% CI, 0.17 to 0.90) which was accounted for by Breslow thickness and ulceration (multivariate HR 0.56, 95% CI, 0.24 to 1.34). Conclusions: The reduced melanoma‐specific survival in nail ALM patients was likely due to their greater thickness and ulceration. Although hand ALMs are thicker and more frequently ulcerated, this is likely due to the higher proportion of nail ALMs present in this location.